Profil Remaja Putri dengan Kejadian Anemia - Intan Renata Silitonga; Nuryeti Nuryeti (Sarana Ilmu Indonesia (salnesia), 2021)
Anemia is a main teenage health problem. Indonesian teenage girl anemia prevalence was 32%. Several factors influencing the anemia condition were knowledge, attitude, and economic level. The aim of this study was knowing relationship the teenage profile of anemia. Hipothesis nol was there were no correlation between knowledge and anemia, no correlation between attitude and anemia, no correlation between economic level and anemia. The method of this study was analytic, cross-sectional, total sampling, and data analysed unviariat and bivariat. Inclution criteria was teenage girls of class 9 at SMPN 9 Cimahi that agreed to join the study and exclution criteria was teenage girl not attending school. We tested the haemoglobine level using digital haemometer. We used questionnaire for attitude and knowledge. The results were 54 teenage girls, 31,5% had anemia, 70,4% with good knowledge, 61,1% positive attitude, and 57,4% low economic level. Most of the anemia teenagers had low knowledge (70,6%), negative attitude (88,3%), low economic level (41,9%). There were correlation between knowledge, attitude, and economic level with anemia (p value <0,05). We concluded that almost half teenagers had anemia, with good knowledge, positive attitude, and low economic level. The anemia teenagers had low knowledge, negative attitude, and low economic level. Hipothesis one was accepeted that were correlation between knowledge and anemia, correlation between attitude and anemia, and correlation between economic level and anemia.